Spatial and temporal variations, and socioeconomic drivers of air quality: case study of the Beijing-Tianjin-Hebei urban agglomeration - Weiqi Wang; Yufeng He; Jingran Gao; Lei Cao; Huanru Ding; Chenhui Liu; Hanqi Tang; Yanfei Chen; Yunlu Zhang (Environmental Research Communications)
Air pollution poses a serious threat to both economic development and public health in China’s heavily polluted Beijing-Tianjin-Hebei region.Realizing a win-win situation for social development and environmental well-being is a pressing issue.This study analyzed panel data from 199 districts in Beijing-Tianjin-Hebei from 2013 to 2020 using various regression models and found that air quality index values decreased by 48.2%. Spatially, the Beijing-Tianjin-Hebei Air Quality Index had a significantly positively correlated spatial correlation that increased over time. Second, energy consumption per unit of gross domestic product and the proportion of construction land had a positive effect on the AQI values of Beijing-Tianjin-Hebei. This implies that increasing energy consumption exacerbates air pollution, particularly in Baoding. Influenced by the urbanization process, the increase in the construction-land ratio was the most significant positive factor, notably in Baoding and Zhangjiakou. Third, there was a negative influence of Research and Development investment and total social retail sales on the Beijing-Tianjin-Hebei Air Quality Index. This finding indicated that increasing Research and Development investment will alleviate air pollution, with most of the counties in the study area benefitting. The collective findings indicate that more prosperous economic areas (such as Beijing and Tangshan) need to pay more attention to air pollution control and that air pollution in the Hebei cluster of heavy industries will be aggravated by the increase in total social retail sales. Based on these results, long-term measures for air pollution control in Beijing-Tianjin-Hebei should focus on reducing energy consumption, slowing urban expansion, and industrial restructuring.